DEVELOPMENT OF THE CONCEPT OF SMART SYSTEMS AND MOBILITY AS A SERVICE: TRENDS OF THE LAST DECADE - PALIANYTSIA, YURII; DUNETS, VASYL; DEDIV, IRYNA; KHVOSTIVSKA, LILIIA; SVERSTIUK, ANDRII (Herald of Khmelnytskyi National University. Technical sciences, 2025)
This article presents a comprehensive analysis of the trends in smart systems and mobility as a service (MaaS) based on publications in the Scopus database from 2014 to 2024. Using a broad search query covering various aspects of smart city technologies, including artificial intelligence devices, the Internet of Things, sustainable development, and mobility services, we identified and analyzed 187,550 relevant publications. The study revealed a significant increase in scientific interest: the number of publications grew from 4,406 in 2014 to 34,948 in 2024. Based on the results of the study, we present an innovative approach to the development of a modular web-based system within the Mobility-as-a-Service (MaaS) concept aimed at improving urban mobility services. The system can function as a stand-alone solution or as an extension of existing mobile web applications commonly used by city residents. Particular attention is paid to the integration of taxi service applications, the use of their continuous background work, and access to geolocation data. The proposed system incorporates artificial intelligence, the Internet of Things, and big data technologies to collect and analyze data in real time, which ensures intelligent transportation management and increases safety. The study introduces several key innovations, including AI-based monitoring modules that use smartphone cameras to assess driver safety, facial recognition for access control, and medical monitoring capabilities through ECG and PKG recording. The system also integrates optimization of delivery and postal services, and emergency medical care, and implements inclusive design features such as voice control and gesture recognition for users with disabilities. The developed solution demonstrates significant potential for improving urban transportation infrastructure, enhancing safety measures, reducing environmental impact, and increasing the accessibility and convenience of mobility services for all citizens. The modular architecture ensures scalability and seamless integration with existing city services, contributing to the promotion of the concept of “smart systems” and sustainable urban development.